Un análisis financiero de la industria española de defensa - RUIZ ARELLANO, Carmen (Journal of the Spanish Institute for Strategic Studies, 2022)
The analysis of the Spanish defense industry is still at an advanced stage due to the lack of adequate information and the little relevance that this topic has in the academic world. In this work an economic-financial approach is made to the Spanish defense industry in order to deepen the knowledge of some features of its structure, conduct and results. To this aim, the classic ECR approach of the Industrial Economics is used. The years 2012 and 2016 have been considered, in order to show the main changes that have taken place as a result of the exit of the economic crisis.